Gfi1 Coordinates Epigenetic Repression of p21(Cip/WAF1) by Recruitment of Histone Lysine Methyltransferase G9a and Histone Deacetylase 1 - Duan, Zhijun (American Society for Microbiology, 2005)
The growth factor independent 1 (Gfi1) transcriptional regulator oncoprotein plays a crucial role in hematopoietic, inner ear, and pulmonary neuroendocrine cell development and governs cell processes as diverse as self-renewal of hematopoietic stem cells, proliferation, apoptosis, differentiation, cell fate specification, and oncogenesis. However, the molecular basis of its transcriptional functions has remained elusive. Here we show that Gfi1 recruits the histone lysine methyltransferase G9a and the histone deacetylase 1 (HDAC1) in order to modify the chromatin of genes targeted for repression by Gfi1. G9a and HDAC1 are both in a repressive complex assembled by Gfi1. Endogenous Gfi1 colocalizes with G9a, HDAC1, and K9-dimethylated histone H3. Gfi1 associates with G9a and HDAC1 on the promoter of the cell cycle regulator p21(Cip/WAF1), resulting in an increase in K9 dimethylation at histone H3. Silencing of Gfi1 expression in myeloid cells reverses G9a and HDAC1 recruitment to p21(Cip/WAF1) and elevates its expression. These findings highlight the role of epigenetics in the regulation of development and oncogenesis by Gfi1.